Endovascular Mechanical Atherothrombectomy (MATH): Using the Rotarex Catheter for Initial Therapy of Acute Lower Limb Ischemia - Bulvas, Miroslav (Archives of Clinical and Medical Case Reports, 2019)
Mechanical atherothrombectomy (MATH) with the Rotarex catheter is rapid, effective and safe technique used as an initial modality for treatment of patients with acute and subacute lower limb ischemia. Contrary to surgery or thrombolysis, this technique has not clinical contraindications and doesn´t require intensive care unit stay. Adoption of MATH has been slow, mainly due to limited experience with the technique and the low standalone efficacy of some devices, neccessitating concomitant use of thrombolysis. The purpose of this review is to present a series of acute arterial occlusions of different anatomy and locations in patients with immediately or marginally threatened extremities.This may help the reader to learn about the technique potential in a vascular emergency states associated with a high mortality and morbidity rates.